FUNDAMENTALS OF FORMATION OF THE PHILOSOPHY OF JADIDISM - Bekchanov Doniyor (Scholar Express Journal, 2021)
This article analyzes the foundations of the formation of the philosophy of Jadidism, the historical conditions of the late XIX and early XX centuries. The main ideas of the philosophy of Jadidism, their role in the process of social development and their political, social, enlightenment and educational significance today are revealed
Keywords: Jadidism; Enlightenment; Independence; Ideas Of Jadidism